The Effective of FlashCard Media for Vulcano Disaster Response and Preparedness Knowlegde - Riwayanti , Adinda Agus; Thohar, Amru Ubaidillah; Rosa, Elvania; Permatasari , Karina Putri; Setyawan, M.Sony; Naufal Alim, Muhammad Shaddam; Sucita, Ni Made Dwi Astini Sucita (Tarqabin Nusantara Group, 2025)
Volcanic eruption guidance is one of the effective strategies in enhancing community preparedness against volcanic eruptions. This guidance involves students of sdn 04 tumpang in grades 3 and 4 as part of a dynamic and strategic disaster mitigation program. The purpose of this guidance is to increase the knowledge and skills of sdn 04 tumpang students in facing volcanic eruptions, as well as to reduce casualties and losses that may occur. During the guidance, students are introduced to the concept of disasters, their impact, the causes of volcanic eruptions, disaster mitigation steps, and the pre-disaster stages of volcanic eruptions. This guidance enhances students' preparedness in facing volcanic eruptions, therefore reducing the negative impacts of this volcanic eruption. The media used in this guidance is flashcards. The materials in the flashcards include the concept of disasters, their impact, the causes of volcanic eruptions, disaster mitigation steps, and the pre-disaster stages of volcanic eruptions, which will be explained by the guidance team or promoters. This activity uses the ADDIE development model (analysis, design, development, implementation, evaluation).